Different cellular landscape of four types of non-diseased cardiac valves contributes to their differences in susceptibility of pathological remodeling and disease. (25th January 2023) - Shu, S; Fu, M; Chen, X; Song, J
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): National Natural Science Foundation of China Background: Exploring the mechanisms of valvular heart disease (VHD) at the cellular level may be useful to identify new therapeutic targets; however, the comprehensive cellular landscape of non-diseased human cardiac valve leaflets remains unclear. Methods: The cellular landscapes of non-diseased human cardiac valve leaflets (five aortic valves, five pulmonary valves, five tricuspid valves, and three mitral valves) from end-stage heart failure patients undergoing heart transplantation were explored using single-cell RNA sequencing (scRNA-seq). Bioinformatics was used to identify the cell types, describe the cell functions, and investigate cellular developmental trajectories and interactions. Differences among the four types of cardiac valve at the cellular level were summarized. Pathological staining was performed to validate the key findings of scRNA-seq. An integrative analysis of our single-cell data and published genome-wide association study-based and bulk RNA sequencing-based data provided insights into the cell-specific contributions to calcific aortic valve diseases. Results: Six cell types were identified among 128, 412 cells from non-diseased human cardiac valve leaflets. Valvular interstitial cells were the largest population, followed by myeloid cells, lymphocytes, valvular endothelial cells, mast cells, and myofibroblasts. The four types of cardiac valve had distinct cellular compositions. The intercellular communication analysis revealed that valvular interstitial cells were at the center of the communication network. The integrative analysis of our scRNA-seq data revealed key cellular subpopulations involved in the pathogenesis of calcific aortic valve diseases. Conclusions: The cellular landscape differed among the four types of non-diseased cardiac valve, which might explain their differences in susceptibility to pathological remodeling and VHD. Cellular landscapes of cardiac valves